Grammatical Cohesion Analysis of Susan Cain’s Speech “The Power of Introverts” - Kadek Novi Krisna Dewi; Gede Irwandika (Austronesian: Journal of Language Science & Literature, 2024)
This study analyzes grammatical cohesion in Susan Cain’s speech with the title The Power of Introverts. This study is addressed to figure out the types of grammatical cohesion and how are the used of grammatical cohesion in speech. In this study, the researcher used descriptive qualitative as the method of analyzing the data. The researcher uses a theory from Halliday and Hasan (1976) to analyze the types of grammatical cohesion and to investigate the use of grammatical cohesion in speech. The finding of this study shows there are two types of grammatical cohesion used in Susan Cain’s speech entitled “The Power of Introverts” namely reference and conjunction.  There are three types of reference found in Susan Cain’s speech “The Power of Introverts,” namely personal reference, demonstrative reference, and comparative reference. Next is conjunction, which is divided into four types such as additive conjunction, adversative conjunction, temporal conjunction, and causal conjunction. However, in this study temporal conjunction is not found in the speech. A personal reference is the type of grammatical cohesion that is the most used in Susan Cain’s speech “The Power of Introverts,” with the number of occurrences 124 items, and the least type of grammatical cohesion found in the speech is a comparative reference with the amount of data 13 items. In conclusion, this study shows that grammatical cohesion is useful in connecting every part of the speech, making the speech easy to understand for the audience or listener, and conveying the information properly.